KALAM INSYA’I THALABI DALAM SYI’R FALSAFAH AL-HAYAH KARYA ELIA ABU MADI: PENDEKATAN ILMU MA’ANI - Zayyin Helmi Holil; Rohanda Rohanda; Khomisah Khomisah (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
This study examines the use of Kalam Insya’i Thalabi in the poem Falsafah al-Hayah by Elia Abu Madi through the perspective of Ilm al-Ma‘ani within the field of Arabic rhetoric (balaghah). The objective of this research is to identify the types of Talabi Insha’i, analyze the structural forms employed, and explore the rhetorical purposes underlying their use, as well as to explain their role in conveying the philosophical values of life presented in the poem. This study employs a descriptive qualitative method with a distributional analysis technique. The data consist of poetic lines containing talabi insha’i structures, which are collected through careful and repeated readings, then identified, classified, and analyzed based on their forms and rhetorical functions.The findings reveal that the main types of Talabi Insha’i found in the poem include amr, nahi, istifham, and nida’, with amr being the most dominant form, while tamanni is not found. Each structure does not merely function as a literal demand but also carries various rhetorical purposes, such as al-irshad, al-inkar, al-zajr, al-nafy and al-iltimas. These findings indicate a close relationship between linguistic form and the philosophical messages conveyed by the poet, particularly in promoting optimism, self-awareness, and acceptance of life’s realities. Therefore, Talabi Insha’i plays a significant role in strengthening meaning, enhancing persuasive effect, and shaping the reflective character of the poem